2013
DOI: 10.1038/nature12076
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchy of orofacial rhythms revealed through whisking and breathing

Abstract: Whisking and sniffing are predominant aspects of exploratory behavior in rodents, yet the neural mechanisms that generate their motor patterns remain largely uncharacterized. We use anatomical, behavioral, electrophysiological, and pharmacological tools to demonstrate that these patterns are coordinated by respiratory centers in the ventral medulla. We delineate a distinct region in the ventral medulla that provides rhythmic input to the facial motoneurons that drive protraction of the vibrissae. Neuronal outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
367
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 306 publications
(393 citation statements)
references
References 56 publications
24
367
1
1
Order By: Relevance
“…3(c)]. In the brainstem, we found that wM1 projects to regions closely associated with whisker movement including facial nucleus 39,40 and a strong innervation of brainstem reticular formation 15,[40][41][42] [ Fig. 3(d)].…”
Section: Projections From Frontal Cortex To Sensorymentioning
confidence: 85%
See 1 more Smart Citation
“…3(c)]. In the brainstem, we found that wM1 projects to regions closely associated with whisker movement including facial nucleus 39,40 and a strong innervation of brainstem reticular formation 15,[40][41][42] [ Fig. 3(d)].…”
Section: Projections From Frontal Cortex To Sensorymentioning
confidence: 85%
“…15,40 wM1 directly innervates facial nucleus 39,40 and prominently innervates brainstem reticular regions, which contain premotor neurons related to whisker movements. [40][41][42] These pathways, and others including those via superior colliculus and striatum (Fig. 3), might contribute to translating action potential firing in wM1 into rhythmic whisker protraction.…”
Section: Functional Roles Of Frontal Cortexmentioning
confidence: 99%
“…Active exploration of flow structure may help the rat distinguish between externally generated flow and flow generated by locomotion, typically near ∼1 m s −1 (Arkley et al, 2014). When taken with the recent discovery that whisking and sniffing are synchronized by a common central pattern generator (Moore et al, 2013), the present work suggests that vibrissotactile sensation may be important to olfactory search behaviors. Neurons in the trigeminal pathway respond strongly to airpuffs, and the present work demonstrates not only that vibrissae are mechanically sensitive to airflow, but also that the rat could actively adjust how the vibrissae respond to airflow.…”
Section: The Mechanics Of Airflow Versus Touchmentioning
confidence: 90%
“…We found significant covariation between the two parameters in only one of the data subsets (continuous substrate, all vibrissae present). However, other physiological or behavioral conditions could favor a coupling between whisking and limb motion, especially if the respiratory rhythm-generating network in the brain stem is working as a mediator between locomotion and facial movements (Moore et al, 2013;Sofroniew et al, 2014).…”
Section: Discussionmentioning
confidence: 99%